Intellectual property rights and international trade of agricultural products - Mercedes Campi; Marco Due\~nas (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2014)
This paper studies the effect of strengthening intellectual property rights (IPRs) after the signing of the TRIPS on agricultural trade and bilateral trade links, for the period 1995-2011. It uses data of agricultural exports and an index of intellectual property (IP) protection that considers specificities of this sector, for a set of 60 economies that allows to study possible divergent results for developed and developing countries. The estimates show that stronger IPRs systems affect negatively total exports and imports of agricultural products, especially for developing countries. At a more disaggregated level, we found heterogeneous results depending on the sub-sectors, but the correlation is negative for most of them. The effect on trade links was investigated using a gravity model and we found that an increase in the IP protection levels is expected to have ambiguous effects depending on the sub-sector and l evel of development of trading country partners. The increase of IP protection of the exporter and the importer was investigated separately and, in some cases, asymmetric effects were found.
Keywords: O1; O34; Q17; F14; 330; Intellectual Property Rights; International Trade; Agriculture; Gravity Model